Development and Initial Evaluation of an Administrative Service Handbook for Psychology Assistants at Yayasan Sinar Talenta: Pengembangan dan Evaluasi Awal Buku Pedoman Layanan Administrasi bagi Asisten Psikolog di Yayasan Sinar Talenta - Isyfi Kholidatur Rohmah; Aniq Hudiyah Bil Haq (Room of Civil Society Development, 2026)
The development of an administrative service handbook for psychology assistants at the Sinar Talenta Foundation was motivated by the need for structured work guidelines in administrative service practices. This activity aimed to develop a handbook that can serve as an initial reference for psychology assistants in understanding workflows, administrative procedures, psychological test administration, client data management, and monthly reporting. The approach used was simple product development with an initial user acceptance evaluation. Initial information on technical needs was obtained through unstructured field observation and communication with the foundation. The handbook was developed through five stages: planning, preparation, writing, editing, and evaluation. The evaluation was conducted using a 1–4 scale questionnaire consisting of 14 items covering content, guide clarity, visual presentation, language, and usability. The initial evaluation by one user showed a total score of 46 out of 56, which falls into the high category. These results indicate that the handbook is considered feasible as an initial internal guide for supporting administrative service standardization at the foundation. However, further evaluation involving more users is needed to examine its broader usability and long-term effectiveness.